Local ageing effects of polymer electrolyte fuel cell membrane electrode assemblies due to accelerated durability testing. Issue 6 (27th November 2022) - Koprek, M.; Schlumberger, R.; Wachtel, C.; Wilhelm, F.; Messerschmidt, M.; Scholta, J.; Hölzle, M.
Abstract: Accelerated durability test (ADT) protocols are useful tools to reduce testing time and development costs of automotive polymer electrolyte fuel cell stacks. Established accelerated stress tests allow comparing individual cell components. However, such tests in general do not allow drawing reliable conclusions on the expected lifetime for a complete stack. In this work, we examine the influence of combined stressors on the ageing behavior of individual cell components operated on stack level. We combine known main stressors for mobile fuel‐cell operation such as dynamic load, temperature and humidity cycling or hydrogen/air fronts during start‐up to develop a new accelerated test protocol. It was applied to an automotive 5‐cell short stack for 460 operating hours (OpH). A second stack was operated in a reference long‐term test for 2300 OpH. Several in situ characterization techniques, such as cyclic voltammetry, and recording the local current density distribution were employed. In addition, post‐mortem analyses, such as focused ion beam scanning electron microscopy imaging, was applied in order to better understand the degradation mechanisms. The results presented here provide an excellent basis for the further development of a new ADT protocol, which will accelerate ageing processes in the fuel cell in a realistic way, i.e. leading to similar degradation characteristics as in long term testing.